SERI Surgical Scaffold in 2-Stage Breast Reconstruction: 2-Year Data from a Prospective, Multicenter Trial. Issue 5 (May 2017) - Karp, Nolan; Choi, Mihye; Kulber, David A.; Downey, Susan; Duda, Gloria; Kind, Gabriel M.; Jewell, Mark L.; Murphy, Diane K.; Lehfeldt, Max R.; Fine, Neil
Abstract : Background: Soft-tissue support devices are used during breast reconstruction. This study investigated long-term clinical data following SERI Surgical Scaffold (SERI) implantation, a bioresorbable, silk-derived scaffold for soft-tissue support. Methods: This was a prospective, multicenter study in 103 subjects who received SERI during stage 1 of 2-stage breast reconstruction with subpectoral tissue expander placement (Natrelle Style 133V; Allergan plc, Dublin, Ireland) followed by subpectoral breast implant placement. Investigator satisfaction (11-point scale: 0, very dissatisfied and 10, very satisfied) at 6 months was the primary endpoint. Ease of use, satisfaction, scaffold palpability/visibility, breast anatomy measurements via 3D images, SERI integration, histology, and safety were also assessed through 2 years after stage 1 surgery. Results: Analyses were performed on the per-protocol population (103 subjects; 161 breasts) with no protocol deviations that could affect outcomes. Ease of use and subject and investigator satisfaction with SERI were high throughout 2 years. Breast anatomy measurements with 3D images demonstrated long-term soft-tissue stability of the lower breast mound. Key complication rates per breast were tissue/skin necrosis and wrinkling/rippling (8.1% each) and seroma, wound dehiscence, and breast redness (5.0% each). Over 2 years, 4 breasts in 4 subjects underwent reoperation with explantation of any device; 2 breasts required SERI explantation. SERI was retained in 98.8% of breasts (159/161) at 2 years. Conclusions: SERI was associated with high and consistent levels of investigator and subject satisfaction and demonstrated soft-tissue stability in the lower breast through 2 years. SERI provides a safe, long-term benefit for soft-tissue support in 2-stage breast reconstruction.